Effects of salicylic acid elicitor against aphids on wheat and detection of infestation using infrared thermal imaging technique in Ismailia, Egypt - mahmoud, mahmoud farag; Mahfouz, Hatem M. (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Wheat (Triticum sativum L.) is one of the most important cereal crops in Egypt. Insectpests, such as aphids, are major threats in terms of yield reduction. Induced resistance in wheat using salicylic acid as a foliar application was tested on the farm of the Faculty of Agriculture, Suez Canal University during 2012/2013 and 2013/2014 seasons. Three wheat cultivars, Gemeza 9, Sakha 93 and Giza 168, were sprayed three times with two concentrations of salicylic acid (SA), 200 mg/l and 100 mg/l, after early detection of aphid infestation by infrared thermal imaging.The infrared thermal imaging technique is based on significant differences in surfacetemperature between infested and healthy leaves. Imaging data are digital, and a computer program can be used to detect infestation rapidly. The results showed that aphid infestation raised the temperature of infested leaves, compared to healthy leaves. The range temperature difference between maximum and minimum temperatures (At) was 1.1 ºC in healthy leaves and 3.9 ºC in infected leaves. The results of SA application showed significant differences in the mean number of aphids and in reduction of infestation among treatments and cultivars. The higher of the two SA rates (200 mg/l) gave higher efficacy in the three cultivars than the lower rate (100 mg/l) over the five weeks of trial. The highest efficacy against aphids was reached one week after application (86.28% for Giza, 85.89% for Gemesa and 70.54% for Sakha). Moreover, SA treatment enhanced the wheat yield of all three cultivars, compared with control plants. The three cultivars (Giza, Gemesa and Sakha) produced higher yields than the control when sprayed with 200 mg/l SA. Their grain yield was 2,491.5, 2,455.0, and 2,327.25 kg/feddan (1 fed = 0.42 ha), respectively. In conclusion, infrared thermal imaging can be employed in identification of infected leaves. Also, the application of SA on wheat induced plant resistance to aphids.
Keywords: Aphids; Wheat; Infestation; Salicylic acids; Thermal imaging